Intratympanic corticosteroid therapy: Hearing impact in unilateral definite Ménière's Disease - A systematic review and meta-analysis - Pedro Manuel Moreira Martins (2020)
Objectives: To evaluate how Intratympanic (IT) Corticosteroid therapy affects hearing levels, through the evaluation of Pure Tone Average (PTA), Speech Discrimination Score (SDS) and hearing change, as well as vertigo control, in unilateral definite Ménière's disease (MD). Methods: A literature search in Pubmed, Web of Science, Cochrane Database and Scopus was performed. The search queries included the terms "intra/transtympanic/topic", "Ménière" and different formulations of corticosteroid therapy. All types of studies were included, regarding they were human based, had full text availability, were in English language, and comprised patients with unilateral definite MD. Initial searches yielded 497 results, with 12 being included in the systematic review and 10 in the meta-analysis, which was performed according to the Preferred Reporting Items for Systematic reviews and Meta-analysis (PRISMA). Results: The PTA levels did not present significant differences 24 months after IT corticosteroid injection: 0.76 [95% CI -1.67; 3.18] dB. Additionally, none of the treatment protocols evaluated offered significant benefits. The same was observed when SDS was evaluated: 24-month difference from baseline was 1.49 [95% CI -1.87; 4.84] %. Hearing did not change in the majority of the patients. Hearing deterioration occurred in a short percentage (0-40%) of patients and a poor vertigo control was associated with it. Complete vertigo control (class A) was observed in 41% of patients at the 24-month mark. Conclusions Intratympanic corticosteroid injection appears to be a safe therapy for MD, as far as hearing levels are concerned. However, due to the low quantity and quality of the studies included, further, better structured trials are needed.